Estimated prevalence of dental caries in athletes: An epidemiological systematic review and meta-analysis - Fellipe Navarro Azeredo; Ludmila Silva Guimarães; Walter Luís; Soares Fialho; Lívia Azeredo Alves Antunes; Leonardo Santos Antunes (Wolters Kluwer Medknow Publications, 2020)
Background: Dental caries is a dysbiotic polymicrobial disease that can cause damage to an individual's successful, elite sporting performance. Aims: This study aimed to realize a meta-analysis to calculate a worldwide, pooled estimated prevalence of dental caries in athletes. Methods and Materials: This systematic review and meta-analysis was registered in PROSPERO (n° CRD42017068127). A systematic search was conducted in the electronic databases Pubmed, Scopus, Web of Science, Virtual Health Library (Lilacs) and Grey literature from inception up to April 2017. The MeSH terms "Sports," Athletes," and "Dental Caries" were used. The inclusion criteria used in this review were observational cross-sectional studies, longitudinal retrospective, and prospective studies that presented the prevalence of dental caries in athletes without intellectual disabilities. From selected articles, the risk of bias tools were assessed. After considering the qualitative heterogeneity among studies, a meta-analysis was conducted. Results: A total of 1,376 abstracts were initially retrieved, with only five meeting the inclusion criteria. Of these, one was considered to have a low risk of bias and four were considered to have a moderate risk of bias. The overall estimated prevalence of dental caries in athletes was 46.25% (95%CI 28.73-64.27). Conclusion: The estimated prevalence of dental caries in athletes, and particularly in athletes from developing countries is considered to be high. The pooled prevalence estimates have important implications in regard to preventive measures and research planning around the world.